Advances in metal halide perovskite nanocrystals: Synthetic strategies, growth mechanisms, and optoelectronic applications. (January 2020) - Li, Yanxiu; Zhang, Xiaoyu; Huang, He; Kershaw, Stephen V.; Rogach, Andrey L.
Graphical abstract: Abstract: Metal halide perovskite nanocrystals, as a new class of light-harvesting and light-emitting materials, have recently attracted a lot of attention for an impressive variety of optoelectronic applications. Some advantages of perovskite nanocrystals include there being low-cost, easy-to-perform synthetic routes, convenient solution processability, precise bandgap tunability over the entire visible spectral range, and exceptionally high photoluminescence quantum yields. In this review, we summarize recent advances of perovskite nanocrystals with an emphasis on the synthetic methods, growth mechanisms, optical properties, and related applications. The focus is placed on emerging new results in terms of the increasing diversity in the synthetic methodologies, ability to control nanoparticle shapes, stability enhancement strategies (including direct syntheses in water), and on the particle formation mechanisms. The basic design principles and up-to-date performance of optoelectronic devices based on perovskite nanocrystals are considered, with a main focus on light-emitting diodes, but also touching upon solar cells, photodetectors, and lasers. We finish the review with a critical outlook into the open issues and future perspective of this versatile, still rapidly developing field.